Measurement of differential cross sections for Higgs boson production in the diphoton decay channel in pp collisions at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Friedl, M; Frühwirth, R; et al. (The European physical journal. C, Particles and fields, 2016)
A measurement is presented of differential cross sections for Higgs boson (H) production in pp collisions at [Formula: see text][Formula: see text]. The analysis exploits the [Formula: see text] decay in data corresponding to an integrated luminosity of 19.7[Formula: see text] collected by the CMS experiment at the LHC. The cross section is measured as a function of the kinematic properties of the diphoton system and of the associated jets. Results corrected for detector effects are compared with predictions at next-to-leading order and next-to-next-to-leading order in perturbative quantum chromodynamics, as well as with predictions beyond the standard model. For isolated photons with pseudorapidities [Formula: see text], and with the photon of largest and next-to-largest transverse momentum ([Formula: see text]) divided by the diphoton mass [Formula: see text] satisfying the respective conditions of [Formula: see text] and [Formula: see text], the total fiducial cross section is [Formula: see text][Formula: see text].